Governments and multinationals : policies in the developed countries - Safarian, A. E.; British-North American Committee; National Planning Association; C.D. Howe Institute (London : British-North American Committee, 1983)
This book comments on four policies being used by developed market countries to regulate inward direct investment by foreign owned multinational enterprises (MNEs). The first two chapters review the evidence of how the 13 countries individually approach these four policies.
Includes bibliographical references p. 105 - 110.
ahz 10/04/2019
Loans
Keywords: Policy making, Government; Policy making; Multinational